Dimensions of Health Service Quality at the Prison Polyclinic Class IIA in Palu City - Valerian, Ivel (Preventif : Jurnal Kesehatan Masyarakat, 2019)
Prisoner services are services related to the implementation of prisoners' rights and obligations in the form of care, coaching, education and guidance. Health services at the Class II A Prison Polyclinic in Palu do not have a health practice permit and only have 5 nurses and 1 dentist.The aim of this study was todetermine the service quality of the Class II A Lapis Polyclinic in Palu. This type of research is quantitative with a descriptive survey approach. The sample in this study were 120 patients who visited the Polyclinic. Sampling used the Accidental Sampling method. Data collected using questionnare. The data obtained were analyzed statistically using univariate analysis. Research results from the dimensions of reliability 86.7% of respondents said well and 13.3% of respondents stated that it was not good, from the dimension of responsiveness 88.3% of respondents said good and 11.7% of respondents stated that it was not good, from the dimensions assurance (guarantee) 85% of respondents stated that good and 15% of respondents stated that it was not good, from the dimensions of empathy (empathy) 94.2% of respondents said good and 5.8% of respondents said it was not good, and from the tangible dimension (physical evidence) 90, 8% of respondents said good and 9.2% of respondents said it was not good. The conclusion of the study, from the service quality at Class II A Prison Polyclinic in Palu based on the SERVQUAL model can be said to be good. Suggestion is to maintain and improve the quality of service from each quality dimension so that it can meet the needs of patients.